2004
DOI: 10.1002/bem.10164
|View full text |Cite
|
Sign up to set email alerts
|

Teratological studies of prenatal exposure of mice to a 20 kHz sawtooth magnetic field

Abstract: In order to evaluate the importance of gestational age in possible effects due to exposure to a 20 kHz sawtooth magnetic field, pregnant ICR mice at gestational 2.5-15.5 days post-coitus, which is the most sensitive stage for the induction of major congenital malformations, were exposed in a carrousel irradiator. The mice were exposed to a 20 kHz intermediate frequency (IF) sawtooth magnetic field had a 6.5 microT peak intensity for 8 h/day. The animals were sacrificed on the 18th day of gestation; and the fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
1
25
1
Order By: Relevance
“…Consistent with reports in the literature, the observed changes were sporadic and did not affect organogenesis in the offspring [17]- [22]. Table 2.…”
Section: Reproductive Performance and Haematological Profilesupporting
confidence: 90%
“…Consistent with reports in the literature, the observed changes were sporadic and did not affect organogenesis in the offspring [17]- [22]. Table 2.…”
Section: Reproductive Performance and Haematological Profilesupporting
confidence: 90%
“…We previously investigated the effect of IF-EMF at a 6.25 mT peak intensity, and found no adverse effect on the fetuses of pregnant mice [Kim et al, 2004]. Therefore, in this study we examined IF-EMF of a 20 kHz magnetic field with a 30 mT peak intensity, which is the limit standard for occupational population.…”
mentioning
confidence: 95%
“…Previous results from laboratory animal studies suggest that IF disturbed the development of animal embryos [Berman et al, 1990;Farrell et al, 1997;Youbicier-Simo et al, 1997]; however, the results have been inconsistent [Juutilainen, 1991;Chernoff et al, 1992;Brent et al, 1993;Huuskonen et al, 1998a] and most studies conducted in mammals reported no or only slight effects on fetus [Tribukait et al, 1987;Stuchly et al, the fetal development of pregnant mice, regardless of gestational age. Consequently, for our current study, we increased the peak intensity of 20 kHz EMF to 30 mT, which is the limit standard for occupational population at 20 kHz in Korea [Yoo, 2002;Kim et al, 2004].…”
mentioning
confidence: 99%
See 2 more Smart Citations